Thrombophilia in 67 Patients With Thrombotic Events After Starting Testosterone Therapy. (September 2016) - Glueck, Charles J.; Prince, Marloe; Patel, Niravkumar; Patel, Jaykumar; Shah, Parth; Mehta, Nishi; Wang, Ping
We compared thrombophilia in 67 cases (59 men and 8 women) with thrombotic events after starting testosterone therapy (TT) versus 111 patient controls having unprovoked venous thrombotic events without TT. In the 67 patients, thrombosis (47 deep venous thrombosis–pulmonary embolism, 16 osteonecrosis, and 4 ocular thrombosis) occurred 6 months (median) after starting TT. Cases differed from controls for factor V Leiden heterozygosity (16 of the 67 [24%] vs 13 [12%] of the 111, P = .038) and for lupus anticoagulant (9 [14%] of the 64 vs 4 [4%] of the 106, P = .019). After a first thrombotic event and continuing TT, 11 cases had a second thrombotic event, despite adequate anticoagulation, 6 of whom, still anticoagulated, had a third thrombosis. Screening for thrombophilia before starting TT should identify men and women at high risk for thrombotic events with an adverse risk–benefit ratio for TT. When TT is given to patients with familial and acquired thrombophilia, thrombosis may occur and recur in thrombophilic men despite anticoagulation.